Estrogen inhibits estrogen receptor α‐mediated rho‐kinase expression in experimental autoimmune encephalomyelitis rats. Issue 7 (25th March 2013) - Feng, Jinzhou; Zhang, Guanghui; Hu, Xiao; Si, Cindy; Qin, Xinyue
ABSTRACT The anti‐inflammatory and neuroprotective effects of estrogen on multiple sclerosis (MS) have been reported in previous studies. Evidence has been found that estrogen can inhibit axonal loss in the MOG‐induced experimental autoimmune encephalomyelitis (EAE) model of MS. Rho‐kinase (ROCK) mediates axonal growth‐inhibitory signals via the Rho/Rho‐kinase pathway. The inhibition of ROCK decreases axonal loss in EAE. However, there is no study reporting the association between estrogen and ROCK in MS and EAE. We examined the anti‐inflammatory and axonal protective effects of estrogen and explored the probable mechanism whereby estrogen inhibits ROCK through ERα in EAE rats. Results show that 17β‐estradiol (E2) can significantly avoid the loss of neurological function in EAE rats. E2 also decreased the infiltration of inflammatory cells and cytokines including IL‐1β, TNF‐α, and IL‐17, but increased the expression of IL‐4. E2 inhibited the expression of ROCK and NF‐200 in EAE rats. The inhibitory effect on ROCK was abolished when nonselective estrogen receptor (ER) antagonist ICI 182780 was added to E2. Furthermore, the expression of ROCK was inhibited by ERα‐selective ligand agonist propyl pyrazole triol. ERβ‐selective ligand WAY‐202041 has no effect on the expression of ROCK. These observations suggest that estrogen inhibits the expression of ROCK in EAE rats and that the inhibitory effects are mediated by ERα rather than ERβ. Synapse 67:399–406, 2013. © 2013 Wiley Periodicals, Inc.